Monolithic Fabrication of NPN/SiN(x) Dual Membrane Cavity for Nanopore-based DNA Sensing - Madejski, Gregory R. (Adv Mater Interfaces, 2019)
Nanoscale preconfinement of DNA has been shown to reduce the variation of passage times through solid-state nanopores. Preconfinement has been previously achieved by forming a femtoliter-sized cavity capped with a highly porous layer of nanoporous silicon nitride (NPN). This cavity was formed by sealing a NPN nanofilter membrane against a substrate chip using water vapor delamination. Ultimately, this method of fabrication cannot keep a consistent spacing between the filter and solid-state nanopore due to thermal fluctuations and wrinkles in the membrane, nor can it be fabricated on thousands of individual devices reliably. To overcome these issues, we present a method to fabricate the femtoliter cavity monolithically, using a selective XeF(2) etch to hollow out a polysilicon spacer sandwiched between silicon nitride layers. These monolithically fabricated cavities behave identically to their counterparts formed by vapor delamination, exhibiting similar translocation passage time variation reduction and folding suppression of DNA without requiring extensive manual assembly. The ability to form nanocavity sensors with nanometer-scale precision and to reliably manufacture them at scale using batch wafer processing techniques will find numerous applications, including motion control of polymers for single-molecule detection applications, filtering of dirty samples prior to nanopore detection, and simple fabrication of single-molecule nanobioreactors.